Weight-loss diets modify glucose-dependent insulinotropic polypeptide receptor rs2287019 genotype effects on changes in body weight, fasting glucose, and insulin resistance: the Preventing Overweight Using Novel Dietary Strategies trial(1)(2)(3) - Qi, Qibin (American Society for Nutrition, 2012)
Background: Glucose-dependent insulinotropic polypeptide [also known as gastric inhibitory polypeptide (GIP)] and its receptor (GIPR) may link overnutrition to obesity, insulin resistance, and type 2 diabetes. A GIPR variant rs2287019 was recently associated with obesity and glucose metabolism. Objective: We aimed to examine whether weight-loss diets that vary in fat content may modify the effect of this variant on changes in body weight, fasting glucose, and insulin resistance in the Preventing Overweight Using Novel Dietary Strategies (POUNDS LOST) trial. Design: We genotyped the GIPR rs2287019 in 737 overweight adults who were randomly assigned to 1 of 4 weight-loss diets that varied in macronutrient contents for 2 y. We assessed the percentage changes in body weight, fasting glucose, and insulin resistance (HOMA-IR) across genotypes by the low-fat and high-fat diets. Results: At 6 mo of diet intervention, the T allele of rs2287019 was associated with greater weight loss (β ± SE: −1.05 ± 0.56%; P = 0.06) and greater decreases in fasting glucose (β ± SE: −2.33 ± 0.86%; P = 0.006), fasting insulin (β ± SE: −8.76 ± 4.13%; P = 0.03), and HOMA-IR (β ± SE: −10.52 ± 4.39%; P = 0.01) in participants who were assigned to low-fat diets, whereas there was no significant genotype effect on changes in these traits in the group assigned to the high-fat diet (all P > 0.44; P-interaction = 0.08, 0.04, 0.10, and 0.07, respectively). After correction for multiple tests (significant P = 0.008), the genotype effect on changes in fasting glucose remained significant. Sensitivity analysis in white participants showed that the interactions were more evident on changes in insulin and HOMA-IR (P-interaction < 0.008). Conclusion: The T allele of GIPR rs2287019 is associated with greater improvement of glucose homeostasis in individuals who choose a low-fat, high-carbohydrate, and high-fiber diet. The POUNDS LOST trial was registered at clinicaltrials.gov as NCT00072995.